Emerging roles and biomarker potential of WNT6 in human cancers - Joana M. Ferreira; Céline S. Gonçalves; Bruno M. Costa (Cell Communication and Signaling)
Abstract The WNT6 ligand is a well-known activator of the WNT signaling pathway, considered a vital player in several important physiologic processes during embryonic development and maintaining homeostasis throughout life, regulating the proliferation and differentiation of multiple stem/progenitor cell types. More recently, as it is the case for many key molecular regulators of embryonic development, dysregulation of WNT6 has been implicated in cancer development and progression in multiple studies. In this review, we overview the most significant recent findings regarding WNT6 in the context of human malignancies, exploring its influence on multiple dimensions of tumor pathophysiology and highlighting the putative underlying WNT6-associated molecular mechanisms. We also discuss the potential clinical implications of WNT6 as a prognostic and therapeutic biomarker. This critical review highlights the emerging relevance of WNT6 in multiple human cancers, and its potential as a clinically-useful biomarker, addressing key unanswered questions that could lead to new opportunities in patient diagnosis, stratification, and the development of rationally-designed precision therapies.